Impact of hemophilia on quality of life of affected children and their parents, a hospital based cross sectional study - Manikandasamy, V.; Arumugasamy, Shanmugam; Mathevan, G. (International Journal of Contemporary Pediatrics, 2017)
Background: Hemophilia can have a huge negative impact not only on the physical health but also on the psychological, economic and social well-being of the affected children and their family. Documentation of this negative impact on quality of life is vital in drawing the attention of relevant stakeholders to design and implement appropriate interventions. Methods: This was a cross sectional study, Children with hemophilia aged 4 to 12 years, and their parents who were attending the Pediatric Hematology Clinic of the Advanced Pediatric Centre, PGIMER, Chandigarh, between July 2009 and June 2010 were included in the study. The Hemo-QoL questionnaire was used to assess the quality of life after translation into local language and validation. Results: The study included 51 children with 10 children in 4-7 years age group and 41 children in 8-12 years age group and their parents. Perceived impact on family (77.3±14.7), poor physical health (62.9±29.8), sports and school (53.8±22.8) had the highest negative impact on QoL. Support from friends, family, and other persons seemed to have contributed positively towards the quality of life. Parents of older children had higher mean subscale scores in View of yourself subscale as compared to parents of younger children (40.8±14.2 vs 23.7±33.0, p value 0.018). Under Sports and school subscale also similar pattern was observed (48.2±20.7 Vs 34.1±13.8, P value 0.045). Conclusions: The Quality of life was poor both among children affected with hemophilia and their parents. Perceived impact on family, poor physical health and inability to participate in school/sports activities are the major contributors to poor QoL. Support from family, friends, and others is vital in maintaining QoL. The QOL worsens with increasing age of the child in both children and their parents.